MXene derived skeleton composite phase change material with strong electromagnetic shielding performance
By introducing MXene derived aerogel skeletons into composite phase change materials, the problems of easy leakage of materials and insufficient thermal conductivity are solved, and the comprehensive improvement of high thermal conductivity, electromagnetic shielding performance and phase change energy storage are achieved.
Patent Information
- Application Number
- CN202510017983.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
Composite phase change materials are prone to leakage during application, and it is difficult to stably exert thermal management and electromagnetic shielding performance.
Using MXene derived aerogel as the framework material, a composite phase change material with stable shape was prepared by vacuum impregnation and adsorption of the molten phase change material. This material uses MXene derived aerogel as a thermal conductivity and conductive filler, and combines a phase change material with a high load capacity to achieve high thermal conductivity and high latent heat.
The shape stability, thermal conductivity and electromagnetic interference shielding efficiency of composite phase change materials have been improved, with thermal conductivity up to 0.64W/m·K, EMI shielding efficiency up to 38.28dB, and enthalpy value of 197.0J/g.
Smart Images

Figure CN119799282A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite phase change material electrothermal energy storage, and relates to a multifunctional composite phase change material having multiple functions such as electrothermal conversion, photothermal conversion, magnetothermal conversion, phase change energy storage, and electromagnetic interference shielding performance. Background Art
[0002] Fossil fuels have always played an important role in the process of human development and have promoted the significant development of human civilization. The global demand for them is becoming more and more urgent. However, the consumption of fossil fuels also produces many side effects, causing irreversible damage to the environment and climate. Greenhouse gas emissions are bound to cause global warming and other phenomena. As of the late 21st century, an assessment of the value of consumable fossil fuel reserves on the earth shows that greenhouse gas emissions will at least increase global temperatures by 2°C. In the contradiction between energy consumption and environmental issues, the top priority is to reduce the pollution caused by existing fuels and develop more economical and efficient green energy.
[0003] Among renewable energy sources, thermal energy storage (TES) is an important form of energy that can effectively solve the spatial and temporal limitations of other renewable resources such as solar energy, wind energy and hydropower. Among them, the thermal energy storage of phase change material (PCM) is a form of energy storage with less temperature restrictions and high efficiency, mainly due to its characteristic of reversibly absorbing and releasing thermal energy during melting and freezing during phase change. At present, many organic solid-liquid phase change materials (SLPCMs) have been widely used in the field of thermal energy storage as latent heat storage materials.
[0004] However, the inherent properties of phase change materials, such as easy leakage, will cause great limitations in their application process and application scenarios. Although encapsulated phase change materials are currently obtained through methods including microencapsulation, porous frame support and electrospinning to solve the leakage problem, the resulting low thermal conductivity once again hinders its application.
[0005] With the widespread application of electronic products, more other properties of phase change materials need to be developed based on the existing performance to make them suitable for application in different scenarios. Among them, improving the thermal conductivity and electromagnetic interference shielding efficiency (EMI SE) of shape-stable composite phase change materials (PCCs) is also an issue that should be concerned about and solved.
[0006] Existing composite phase change materials improve the thermal conductivity of the material by adding different additives, and use shape skeletons or shape stabilization technology to fix the phase change material. The skeleton can not only prevent the leakage of the phase change material, but also enhance the other properties of the phase change material. However, the development of multifunctional phase change materials that combine thermal management and electromagnetic interference shielding, or even more, has become a key problem to be solved at this stage. Summary of the invention
[0007] The purpose of the present invention is to solve the problem that composite phase change materials are prone to leakage and difficult to stably exert thermal management and electromagnetic shielding performance, and to provide a MXene-derived skeleton composite phase change material with strong electromagnetic shielding performance, so as to simultaneously have the functions of electrothermal conversion, photothermal conversion, magnetothermal conversion, phase change energy storage and electromagnetic interference shielding performance.
[0008] To achieve the above-mentioned purpose of the invention, the MXene-derived skeleton composite phase change material with strong electromagnetic shielding performance described in the present invention is a shape-stable composite phase change material obtained by vacuum impregnation and adsorption of molten phase change material using MXene-derived aerogel as the skeleton material, wherein the MXene-derived aerogel is an aerogel-based skeleton material obtained by adding chitosan quaternary ammonium salt (CQS), polyethyleneimine (PEI) and carbon nanotubes (CNTs) to a MXene aqueous dispersion to obtain a mixed solution, which is then directionally rapidly frozen in liquid nitrogen, vacuum freeze-dried, and carbonized at high temperature.
[0009] More specifically, the mass ratio of the raw material MXene used to prepare the aerogel-based skeleton material to CQS, PEI, and CNTs is preferably 1:0.3-1:1.3-4:0.6-2.
[0010] Furthermore, the phase change material may be any one of polyethylene glycol (PEG), paraffin, lauric acid or octadecane.
[0011] The present invention uses the MXene-derived aerogel as a thermal conductor and a conductive filler, and obtains a novel multifunctional composite phase change material with a high loading amount after impregnation and adsorption of the phase change material. The loading amount of the phase change material can reach more than 98% of the total mass of the composite phase change material.
[0012] Furthermore, the present invention also provides a method for preparing the composite phase change material, which specifically comprises: 1) Prepare MXene suspension, add chitosan quaternary ammonium salt, polyethyleneimine and carbon nanotubes, mix and disperse them evenly, freeze them quickly and freeze dry them in a freeze dryer to obtain aerogel framework material; 2) Carbonizing the aerogel framework material at 380-400°C to obtain MXene-derived aerogel; 3) The MXene-derived aerogel and the excess molten phase change material are vacuum impregnated to obtain a MXene-derived skeleton composite phase change material.
[0013] Specifically, the directional rapid freezing is to put the mixed solution into a polytetrafluoroethylene mold with a copper plate at the bottom, and immerse it in liquid nitrogen for rapid directional freezing. The directional rapid freezing described in the present invention is completed with the help of a specific mold, the entire mold is polytetrafluoroethylene, and only the bottom is set as a copper plate, so that the heat of the mixed solution can only be exchanged with liquid nitrogen through the bottom copper plate in a directional and rapid manner, thereby forming an ice crystal structure from bottom to top.
[0014] More specifically, the high temperature carbonization time of the aerogel frame material of the present invention is preferably 2 to 3 hours.
[0015] More preferably, the present invention is to vacuum impregnate the MXene-derived aerogel in an excess of molten phase change material for 8 to 12 hours to fully absorb the molten phase change material.
[0016] The present invention introduces a MXene-derived aerogel skeleton into the phase change material to prepare a composite phase change material with stable shape, high thermal conductivity and high latent heat. At the same time, the composite material also has EMI shielding function and electrothermal, photothermal and magnetothermal conversion capabilities. The thermal conductivity of the composite phase change material can reach up to 0.64W / m·K, and the EMI shielding effectiveness (SE) is as high as 38.28dB, which is much higher than the commercial standard (20dB), and the enthalpy value is 197.0J / g. From the perspective of comprehensive performance, the combination of the prepared MCPC aerogel with diversified performance and the phase change material can further protect the human body and electronic equipment from electromagnetic pollution other than thermal runaway. It has broad application prospects in electrothermal, photothermal, magnetothermal, energy storage, and thermal management of electronic equipment, and is a potential electronic packaging material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a synthesis flow chart of the composite phase change material of the present invention.
[0018] Figure 2 These are the SEM images and EDS spectra of the composite phase change material.
[0019] Figure 3 This is the BET test diagram of the composite phase change material.
[0020] Figure 4 It is the DSC, TGA curve and leakage rate test results of the composite phase change material.
[0021] Figure 5 It is the infrared thermal imaging and thermal conductivity diagram of composite phase change materials.
[0022] Figure 6This is a test chart of the EMI shielding and magnetothermal conversion performance of composite phase change materials.
[0023] Figure 7 It is the electrothermal conversion diagram of composite phase change material.
[0024] Figure 8 It is a diagram of the light-to-heat conversion of composite phase change materials.
[0025] Fig. 9 This is a thermal runaway data chart of a battery wrapped with composite phase change materials. Implementation
[0026] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.
[0027] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0028] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.
[0029] The raw material MXene suspension used in the embodiment of the present invention is prepared by etching Ti3AlC2 MAX phase precursor with LiF. Specifically, 2g LiF is added to 30mL of 12M HCl solution, stirred continuously for 30min, 2g Ti3AlC2 MAX phase precursor is added, stirred at 35°C for 24h, and the Al layer is etched away; deionized water is added to the solution after etching, centrifuged at 8000rpm for 10min, the supernatant is discarded, deionized water is continued to be added, and the above operation is repeated 6 to 7 times until the pH value of the supernatant is 6, and the washing is completed; the product is placed in 0-30°C low-temperature ethanol, and ultrasonicated at 40kHz for 10min under an inert atmosphere, during which ice bags or ice cubes are used for cooling, and the dark green supernatant containing layered MXene nanosheets is collected as the raw material of the MXene suspension.
[0030] The above MXene suspension was mixed with PEI and CQS aqueous solutions, and then CNT aqueous dispersion was added and mixed evenly, placed in a polytetrafluoroethylene mold with a copper plate at the bottom, immersed in liquid nitrogen for rapid direction freezing, vacuum dried in a freeze dryer, and then carbonized at 400°C to obtain MXene-derived aerogel.
[0031] The PEG material was fully adsorbed in the MXene-derived aerogel by vacuum impregnation method to prepare the PEG@MCPC composite phase change material. Example
[0032] Example 1
[0033] 0.2 g of CNT was weighed and placed in a beaker with 20 mL of deionized water, and ultrasonically dispersed for 1 h to obtain a CNT aqueous dispersion.
[0034] A PEI aqueous solution with a concentration of 10 wt % and a CQS aqueous solution with a concentration of 2.5 wt % were prepared respectively.
[0035] like Figure 1 As shown, 15 mL of MXene suspension was added to a beaker, and then 5 mL of PEI aqueous solution and 5 mL of CQS aqueous solution were added, and magnetic stirring was performed for 30 min to obtain a mixed solution after uniform dispersion.
[0036] The above CNT aqueous dispersion was added to the mixed solution, stirred for 0.5 h, and then placed in a polytetrafluoroethylene mold with a copper plate at the bottom. After being immersed in liquid nitrogen for directional rapid freezing, the mold was placed in a vacuum freeze dryer and dried for 48 h.
[0037] The dried product was taken out, placed in a tubular furnace, heated to 400 °C and carbonized for 2 h to obtain a MXene-derived aerogel, which was recorded as MCPC-1.
[0038] The MCPC-1 prepared above was placed in a beaker containing excess PEG by vacuum impregnation method and placed in a vacuum oven at 80°C to allow MCPC-1 to fully absorb the molten PEG. After repeated vacuum adsorption three times, the excess PEG on the surface of MCPC-1 was removed with filter paper to obtain a shape-stable composite phase change material, which was recorded as PEG@MCPC-1.
[0039] Example 2
[0040] Except that the 15 mL MXene suspension in Example 1 was changed to 30 mL, the rest was the same as Example 1, and a shape-stable composite phase change material was prepared, which was recorded as PEG@MCPC-2.
[0041] The microstructure of the prepared PEG@MCPC-2 material was characterized. Figure 2(a) to (d) first give the SEM images of the MXene-derived aerogel skeleton at different magnifications. It can be seen that MXene has a sheet structure, and CQS is attached to the MXene sheet, playing the role of supporting the skeleton, forming a stable three-dimensional structure together with CNT and PEI. The entire MCPC skeleton is an interconnected network structure with a large number of voids distributed in it, providing a large number of adsorption sites for phase change materials. Figure 2 (e) to (d) further provide SEM images after PEG adsorption, from which it can be seen that PEG is filled into the voids of MCPC, and the three-dimensional structure of MCPC can still be clearly observed in the composite phase change material after PEG adsorption.
[0042] Further by Figure 2 As can be seen from (i) in the MCPC skeleton structure, due to the presence of MXene nanosheets and PEI, a series of signals corresponding to C, O, N, F, Cl, and Ti elements appear in the elemental mapping diagram, and show a uniform and dense distribution in the aerogel skeleton; and (j) after the MCPC aerogel skeleton adsorbs PEG, the C and O signals in the mapping spectrum are strong, almost covering the other element signals from CQS, PEI, and MXene nanosheets. This result shows that the aerogel skeleton has been completely impregnated with PEG, and PEG accounts for a large proportion in the overall composite phase change material.
[0043] Example 3
[0044] The 15 mL MXene suspension in Example 1 was replaced with 45 mL, and the rest was the same as Example 1. A shape-stable composite phase change material was prepared according to the method of Example 1, which was recorded as PEG@MCPC-3.
[0045] The MXene-derived aerogel skeletons prepared in Examples 1 to 3 were subjected to BET testing using Micromeritics ASAP 2460. Figure 3 The adsorption-desorption curves and pore size distribution of the materials are given. After calculation, it can be obtained that the specific surface areas of MCPC-1, MCPC-2 and MCPC-3 are 162.2748 m 2 / g, 144.3885m 2 / g and 146.3214m 2 / g.
[0046] This high specific surface area and porous structure enable the aerogel skeleton to absorb a large amount of phase change materials, especially for solid-liquid phase change materials with large molecular chains such as PEG. The different pore size distributions and their surface tension and capillary force can provide PEG with the ability to be difficult to disperse and maintain its state when it is in liquid state. At the same time, MCPC can also provide mutual support with PEG, improve the mechanical properties of the material, and reduce the leakage rate of the composite phase change material in a thermal environment.
[0047] Example 4
[0048] The MCPC-1 prepared in Example 1 was placed in a beaker containing excess lauric acid and placed in a vacuum oven at 80°C to allow the MCPC-1 to fully absorb the molten PEG. After repeated vacuum adsorption three times, the excess PEG on the surface of the MCPC-1 was removed with filter paper to obtain a shape-stable phase-change composite material, which was recorded as lauric acid@MCPC-1.
[0049] Application Example 1
[0050] In order to further understand the heat absorption and release capacity of the composite phase change material prepared in the present invention compared with PEG, the composite phase change materials prepared in Examples 1 to 3 and pure PEG were tested by differential scanning calorimetry using TA Q20 at a heating and cooling rate of 4°C / min in a nitrogen atmosphere, and the results were as follows: Figure 4 In the DSC curve of (a), the phase change enthalpy of PEG@MCPC-2 and PEG@MCPC-3 reached an astonishing 197.0 J / g, which is 94.8% of the phase change enthalpy of PEG. The phase change enthalpy of PEG@MCPC-1 also reached 183.4 J / g, which is 88.3% of the phase change enthalpy of PEG. Both have good phase change energy storage capacity.
[0051] Then, each material was heated from room temperature to 800°C in a nitrogen atmosphere at a heating rate of 10°C / min to obtain Figure 4 The TGA test results shown in (b) show that pure PEG begins to decompose at around 390°C and is basically decomposed at 420°C. The TGA curves of each PEG@MCPC are similar to those of PEG. The reason is that MCPC has a strong adsorption capacity for PEG, which makes the vast majority of PEG@MCPC PEG, and the skeleton and impurities that account for a very small proportion are not enough to affect the general direction of the curve.
[0052] Figure 4 (c) and (d) are the leakage rate test results of PEG and PEG@MCPC. The specific test is to weigh the material, put it in a culture dish with filter paper, move it into a 90℃ electric blast oven, take pictures and record it every 20 minutes, take it out of the oven after 1 hour to cool down, scrape off the leaked PEG, record the material mass, and calculate the leakage rate.
[0053] Among them, pure PEG leaked completely after 60 minutes, while under the action of MCPC, only a small amount of PEG in the composite phase change material leaked.
[0054] Application Example 2
[0055] Figure 5 The infrared thermal imaging performance test results of the composite phase change materials prepared in Examples 1 to 3 are provided. Different composite phase change materials PEG@MCPC are placed on a heating table for heating, and the temperature change data of PEG@MCPC and the heating plate over time are collected by an infrared thermal imager. Figure 5 It can be seen from the infrared thermal imaging data of (a) and (c) that under the heating of the heating table, the temperature of PEG@MCPC begins to rise slowly. After 2000s, the temperature is basically stable and is far lower than the temperature of the heating table. This is attributed to the fact that PEG@MCPC has good heat dissipation ability and heat absorption and heat dissipation have reached a balance, so the temperature remains basically unchanged.
[0056] Figure 5 (b) is the thermal conductivity data of PEG@MCPC. PEG@MCPC-1 has the lowest thermal conductivity, only 0.52 W / m·K, while the highest PEG@MCPC-3 reaches 0.64 W / m·K.
[0057] Application Example 3
[0058] With the development of electronic products, the electromagnetic wave radiation (EMW) generated will not only affect the performance of electronic devices themselves, but also endanger human health. Therefore, it is also very important to prepare multifunctional composite phase change materials with electromagnetic shielding while meeting the requirements of thermal management.
[0059] Figure 6 (a) shows the mechanism diagram of the incident electromagnetic wave propagating in the composite phase change material PEG@MCPC of the present invention. When the incident electromagnetic wave propagates to the surface of the composite phase change material, due to the impedance mismatch between the composite phase change material and the air, the electromagnetic wave is reflected and propagated to the internal structure of the composite phase change material. The MXene nanosheets in the composite phase change material form a tight and continuous electron transmission channel through rapid directional freezing, so that the electromagnetic wave is repeatedly reflected and scattered in the channel to dissipate. At the same time, the conductive network formed inside the composite phase change material also provides an effective way for electron migration and crossing, thereby inducing the phenomenon of conductive loss. Furthermore, due to the characteristics and local defects of the MXene surface containing rich functional groups such as -OH and -F, dipole polarization and interface polarization occur, which also causes the incident electromagnetic wave to dissipate. Through the above-mentioned phenomena and characteristics, the MCP@PEG composite phase change material has excellent electromagnetic shielding performance.
[0060] like Figure 6 As shown in (b-d), the EMI SE values of PEG@MCPC-1, PEG@MCPC-2 and PEG@MCPC-3 are about 22.43dB, 34.77dB and 38.28dB respectively, which are far beyond the commercial requirements of electromagnetic shielding materials (20dB), among which PEG@MCPC-3 has the highest EMI SE value. With the increase of MXene content in PEG@MCPC, the EMI SE value will also increase. The main reason is that the MXene sheets are arranged in a directional and regular manner along the parallel direction, forming a flowing conductive network, thus forming a more complete and compact three-dimensional porous conductive network.
[0061] SE of PEG@MCPC in the figure A Much higher than the corresponding SE R , indicating that the mechanism of EMW attenuation is mainly through absorption rather than reflection. With the effective continuous network of MXene, SE T and SE A The trend is upward, while SE R The impedance matching is always kept below 3dB. The enhanced impedance matching allows EMWs to enter the composite phase change material by incident instead of direct reflection. A The proportion of SE T played a decisive leadership role.
[0062] Ti3C2T x The rich carrier surface on the surface spontaneously migrates between the sheets and generates microcurrents, which can attenuate energy in the form of ohmic loss by converting energy into heat. In view of its special properties, the present invention has carried out magnetothermal conversion performance tests. Figure 6 (e~g) provide the magnetothermal conversion data of composite phase change materials.
[0063] PEG@MCPC was placed inside the copper coil, a voltage was applied to both ends of the copper coil to form a stable electromagnetic field, and multiple layers of A4 paper were placed between the copper coil and PEG@MCPC to reduce the ohmic heat of the copper coil. The magnetothermal conversion performance was tested, and an infrared thermal imager was used to collect the temperature change curve of PEG@MCPC over time. It can be observed from the figure that as time goes by, the temperature of PEG@MCPC rises rapidly and tends to balance, and the temperature rise rate accelerates as the magnetic field strength increases.
[0064] Application Example 4
[0065] The electrothermal conversion performance of the composite phase change material was tested. Figure 7 (a) shows the schematic diagram of the structure of the electrothermal conversion device, which mainly consists of a DC power supply, an infrared thermal imager and a data collection system. Figure 7(b) is the electrical conductivity of the composite phase change material. It can be seen that the electrical conductivity of the composite phase change material increases with the increase of MXene content.
[0066] Figure 7 (c~h) show the electrothermal conversion data of PEG@MCPC-1, PEG@MCPC-2 and PEG@MCPC-3 respectively, and the voltage conditions are set to 7V, 10V, 13V and 16V respectively, where (c~e) is the highest temperature and (f~h) is the average temperature. In the figure, during the application of voltage, the temperature of the composite phase change material increases significantly, so the composite phase change material has good electrothermal conversion ability, heat storage performance and management performance, and has good application prospects in the field of intelligent temperature control of electronic equipment.
[0067] Application Example 5
[0068] To further study the photothermal conversion ability of PEG@MCPC, a Figure 8 In the device shown in (a), the PEG@MCPC is placed in a light-proof black box and a 130 mW / cm 2 An incandescent lamp was used to simulate sunlight, and a thermocouple was placed on the upper surface of PEG@MCPC to collect temperature change data, which was then transmitted to a computer and recorded via a data acquisition device.
[0069] like Figure 8 In (b), the light absorption capacity of PEG@MCPC in the range of 200-230 nm is mainly determined by the content of CNT, while in the range of 230-800 nm, the content of MXene has a stronger influence on PEG@MCPC. In general, PEG@MCPC has good light absorption capacity in the range of 200-800 nm.
[0070] Figure 8 (c) is a photothermal conversion data graph. It can be observed that the temperature of the composite phase change material gradually increases with the illumination time. When the temperature reaches the phase change temperature, the temperature rise slows down or even remains unchanged. After the phase change is completed, the temperature continues to rise. Therefore, the composite phase change material has good photothermal conversion ability.
[0071] Application Example 6
[0072] The present invention tests the effect of PEG@MCPC-3 wrapped 18650 batteries (nominal capacity 2550mAh, energy density 204Wh / kg, standard cycle number 1000 times) on battery thermal runaway by an adiabatic accelerating calorimeter (ARC, BAC-90A, Young Instrument).
[0073] Fig. 9(a) shows the thermal runaway data of the battery, and (b) is an enlarged view of the heating gradient temperature rise stage. It can be seen that the battery without the wrapped composite phase change material completed the gradient temperature rise after 16286s, while the gradient temperature rise time of the battery wrapped with PEG@MCPC-3 reached 38328s. Compared with the two, the thermal runaway temperature was delayed by 40077s, the thermal runaway temperature increased by 15.01℃, and the peak temperature of the thermal runaway decreased by 107.31℃, indicating that PEG@MCPC has a good effect of delaying the occurrence time of thermal runaway and reducing the degree of thermal runaway hazard.
[0074] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. A MXene-derived skeleton composite phase change material with strong electromagnetic shielding performance is a shape-stable composite phase change material obtained by vacuum impregnation and adsorption of molten phase change material using MXene-derived aerogel as the skeleton material, wherein the MXene-derived aerogel is an aerogel-based skeleton material obtained by adding chitosan quaternary ammonium salt, polyethyleneimine and carbon nanotubes to a MXene aqueous dispersion to obtain a mixed solution, which is directionally rapidly frozen in liquid nitrogen, vacuum freeze-dried, and carbonized at high temperature.
2. The MXene-derived skeleton composite phase change material according to claim 1, characterized in that The mass ratio of the raw material MXene to chitosan quaternary ammonium salt, polyethyleneimine and carbon nanotubes used to prepare the aerogel-based skeleton material is 1:0.3-1:1.3-4:0.6-2.
3. The MXene-derived skeleton composite phase change material according to claim 1, characterized in that The phase change material is any one of polyethylene glycol, paraffin, lauric acid or octadecane.
4. The MXene-derived skeleton composite phase change material according to claim 1, characterized in that The loading amount of the phase change material in the MXene-derived skeleton composite phase change material is not less than 98%.
5. The method for preparing the MXene-derived skeleton composite phase change material according to claim 1, comprising: 1) Prepare MXene suspension, add chitosan quaternary ammonium salt, polyethyleneimine and carbon nanotubes, mix and disperse them evenly, freeze them quickly and freeze dry them in a freeze dryer to obtain aerogel framework material; 2) Carbonizing the aerogel framework material at 380-400°C to obtain MXene-derived aerogel; 3) The MXene-derived aerogel and the excess molten phase change material are vacuum impregnated to obtain a MXene-derived skeleton composite phase change material.
6. The preparation method according to claim 5, characterized in that The directional rapid freezing is to put the mixed solution into a polytetrafluoroethylene mold with a copper plate at the bottom, and immerse it in liquid nitrogen for rapid directional freezing.
7. The preparation method according to claim 5, characterized in that The high temperature carbonization time is 2 to 3 hours.
8. The preparation method according to claim 5, characterized in that The vacuum impregnation time is 8 to 12 hours.
Citation Information
Cited By
Preparation method of self-adaptive anti-electromagnetic interference composite material
CN120271889A
Preparation method of self-adaptive electromagnetic interference resistant composite material
CN120271889B